Emerging Cellular Therapies for Anti-myeloperoxidase Vasculitis and Other Autoimmune Diseases - Odobasic, Dragana; Holdsworth, Stephen R. (Frontiers in Immunology, 2021)
Anti-myeloperoxidase vasculitis (MPO-AAV) is a life-threatening autoimmune disease which causes severe inflammation of small blood vessels, mainly in the kidney. As for many other autoimmune diseases, current treatments, which consist of general immunosuppressants, are partially effective, toxic and broadly immunosuppressive, causing significant and serious adverse effects in many patients. Therefore, there is an urgent need for more targeted and less harmful therapies. Tolerogenic dendritic cells, regulatory T cells and stem cells have emerged as attractive, new and safer options for the treatment for various autoimmune diseases due to their unique and selective immunosuppressive capacity. In this review, we will discuss how these cellular therapies offer potential to become novel and safer treatments for MPO-AAV.